Aeroelasticity of compliant span morphing wings. (21st September 2018) - Ajaj, Rafic M; Friswell, Michael I
Abstract: A low-fidelity aeroelastic model is developed to study the dynamic behaviour of uniform, cantilever span morphing wings. The wing structure is modelled using the shape functions of the bending and torsional modes of a uniform cantilever wing according to the Rayleigh–Ritz method. Theodorsen's unsteady aerodynamic theory is used to model the aerodynamic loads. A Padé approximation for the Theodorsen's transfer function is utilised to allow time-domain simulation and analysis. The sensitivity of the aeroelastic behaviour of span morphing wings to different geometric parameters and mechanical properties is considered. Furthermore, the impact of morphing rate on the aeroelastic behaviour is studied. Finally, the use of two novel span morphing concepts for flutter suppression is assessed.